Discovery and registration of components in multimodal systems distributed on the IoT. (December 2015) - Rodriguez, B. Helena; Moissinac, Jean-Claude
Abstract: One of the major gaps in the current HTML5 web platform, is the lack of interoperable means for a multimodal application to discover services and applications available in a given space and network for example, in smart houses or in applications for the Internet of Things. To address this gap, we produced a SOA approach that was submitted to the W3C׳s Multimodal Working Group and validated as a draft recommendation that aims to allow the discovery and registration of components used in multimodal systems for the web of things. In this approach, the components are described and virtualized in a module communicating through two dedicated events, they are registered in a Resources Manager to facilitate the fine management of concurrent multimodal interactions, and the system supports an interoperable discovery, registration and filtering of the features provided by heterogeneous and dynamic components in the web of things. In this paper we will present the W3C׳s Multimodal Architecture and Interfaces standard and explain the Discovery and Registration mechanism adopted to address the need of finding and integrating components into distributed and dynamic multimodal systems.